The role of the GABA system in amphetamine-type stimulant use disorders - Jiao, Dongliang; liu, Yao; Li, Xiaohong; liu, Jinggen; Zhao, Min (Frontiers in Cellular Neuroscience, 2015)
Abuse of amphetamine-type stimulants (ATS) has become a global public health problem. ATS causes severe neurotoxicity, which could lead to addiction and could induce psychotic disorders or cognitive dysfunctions. However, until now, there has been a lack of effective medicines for treating ATS-related problems. Findings from recent studies indicate that in addition to the traditional dopamine-ergic system, the GABA (gamma-aminobutyric acid)-ergic system plays an important role in ATS abuse. However the exact mechanisms of the GABA-ergic system in amphetamine-type stimulant use disorders are not fully understood. This review discusses the role of the GABA-ergic system in ATS use disorders, including ATS induced psychotic disorders and cognitive dysfunctions. We conclude that the GABA-ergic system are importantly involved in the development of ATS use disorders through multiple pathways, and that therapies or medicines that target speciﬁc members of the GABA-ergic system may be novel effective interventions for the treatment of ATS use disorders.